Real quadratic

Algebra Level pending

The expression a x 2 + 3 x 4 3 x 4 x 2 + a \dfrac{ax^2+3x-4}{3x-4x^2+a} can assume all real values for all real values of x x is under a condition that a [ b , c ] { d } a \in [b,c] \cup \{d \} , where b , c , d b,c,d are integers.

Find b + c + d . b+c+d.


The answer is 4.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Tom Engelsman
May 20, 2021

Upon examination, the value a = 4 a = -4 in the denominator has no real zeros due to x = 3 ± 9 4 ( 4 ) ( 4 ) 8 = 3 55 i 8 \large x = \frac{-3 \pm \sqrt{9-4(-4)(-4)}}{-8} = \frac{3 \mp \sqrt{55}i}{8} , which reduces the rational function f ( x ) = a x 2 + 3 x 4 4 x 2 + 3 x + a \large f(x) = \frac{ax^2+3x-4}{-4x^2+3x+a} to 1 1 for all x R . x \in \mathbb{R}.

The other way f ( x ) : R R f(x): \mathbb{R} \rightarrow \mathbb{R} remains valid occurs iff f ( x ) 0 f'(x) \neq 0 over x R . x \in \mathbb{R}. Its derivative computes to:

f ( x ) = ( 2 a x + 3 ) ( 4 x 2 + 3 x + a ) ( 8 x + 3 ) ( a x 2 + 3 x 4 ) ( 4 x 2 + 3 x + a ) 2 = ( 3 a + 12 ) x 2 + 2 ( a 2 16 ) x + ( 3 a + 12 ) ( 4 x 2 + 3 x + a ) 2 0 \large f'(x) = \frac{(2ax+3)(-4x^2+3x+a)-(-8x+3)(ax^2+3x-4)}{(-4x^2+3x+a)^2} = \frac{(3a+12)x^2+2(a^2-16)x+(3a+12)}{(-4x^2+3x+a)^2} \neq 0 ;

which will be satisfied when ( 3 a + 12 ) x 2 + 2 ( a 2 16 ) x + ( 3 a + 12 ) 0 (3a+12)x^2+2(a^2-16)x+(3a+12) \neq 0 , or x = 2 ( a 2 16 ) ± 4 ( a 2 16 ) 2 4 ( 3 a + 12 ) 2 2 ( 3 a + 12 ) \large x = \frac{-2(a^2-16) \pm \sqrt{4(a^2-16)^2 - 4(3a+12)^2}}{2(3a+12)} ;

or x = ( 16 a 2 ) ± ( a + 4 ) 2 ( a 4 ) 2 9 ( a + 4 ) 2 3 a + 12 ; \large x = \frac{(16-a^2) \pm \sqrt{(a+4)^2(a-4)^2 -9(a+4)^2}}{3a+12};

or x = ( 4 + a ) ( 4 a ) ± ( 4 + a ) ( a 4 ) 2 9 3 ( a + 4 ) ; \large x = \frac{(4+a)(4-a) \pm (4+a)\sqrt{(a-4)^2 - 9}}{3(a+4)};

or x = ( 4 a ) ± a 2 8 a + 7 3 ; \large x = \frac{(4-a) \pm \sqrt{a^2 -8a + 7}}{3};

or x = ( 4 a ) ± ( a 1 ) ( a 7 ) 3 ; \large x = \frac{(4-a) \pm \sqrt{(a-1)(a-7)}}{3};

which requires ( a 1 ) ( a 7 ) 0 1 a 7 (a-1)(a-7) \le 0 \Rightarrow 1 \le a \le 7 . Hence, the result is a [ 1 , 7 ] { 4 } 1 + 7 4 = 4 . a \in [1,7] \cup \{-4\} \Rightarrow 1 + 7 - 4 = \boxed{4}.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...